Multi-stakeholder framework for intervening in RTB seed systems: user’s guide - CGIAR Research Program on Roots, Tubers and Bananas (International Potato Center, 2016)
Root, tuber, and banana (RTB) crops are important for food security and commerce, especially in the tropics. They are vegetatively reproduced, so unlike crops grown from true seed. RTBs face unique challenges-they are bulky, perishable, and susceptible to pests (especially diseases)-and their seed systems have suffered from low investments. This user’s guide presents a tool, called the multi-stakeholder framework for intervening in RTB seed systems. It is designed to help any interested person to understand RTB seed systems or to improve interventions (e.g., projects or programs) in them. The frameworks may be graphed as a table, with rows of stakeholders (e.g., policymakers, researchers, and seed producers) and columns of characteristics: availability of seed, access, and quality. Access includes delivery channels, affordability, and awareness. Seed quality includes crop variety and other issues (health, genetic purity, physiological age, and physical quality). Gender should always be taken into account when using the framework. The framework can be used to plan a future intervention or to analyze the recent history of one. When used before an intervention, the framework may guide a study of the existing seed system and identify bottlenecks and key actions for the upcoming intervention. When used to monitor an ongoing intervention, the framework can help to plan the evolution of activities, scope, theory of change (including assumptions about farmers and seed), objectives, and impacts. The framework will help stakeholders to think about RTB seed systems in a holistic way and to account for differences-even contradictions-in the perspectives of some of the people and organizations who are the stakeholders in these crops.